From Paper to Screen: Exploring the Effectiveness of Digital Charts in Teaching Modals - Lungguh Halira Vonti; Pujiati; Mullynanda Pontiaka; Artika Riestiyaningtyas; Muhammad Pandu DaniAji (Universitas Islam Negeri Palopo, 2025)
Providing a good chart makes a good impact as well for the learning, especially students’ understanding. This classroom action research aimed to enhance senior high school students’ understanding of English modals through the use of multimodal digital chart media. The study was conducted in two cycles at a senior high school in Bogor, involving 31 students of XI grade. Each cycle consists of: planning, action, observation, and reflection. The study employed a mixed-methods design; collecting data through pre-tests, post-tests, and documentation including feedback from the English teacher and students’ test scores analyzed via Quizizz. In the first cycle, static printed charts were used. Due to unclear layout and small font size, students’ engagement and comprehension remained limited, as reflected in the average post-test score of 62%, up from 50% in the pre-test. In the second cycle, digital charts were integrated into PowerPoint presentations, which offered clearer visualization and better accessibility. This resulted in improved understanding, with average scores rising from 66% in the pre-test to 71% in the post-test. The result shows that well-designed digital charts combining visuals, keywords, and structured content can significantly improve students’ grasp of abstract grammatical topics like modals. The study recommends incorporating visually engaging, relevant, and culturally appropriate digital media to support English language teaching and to foster deeper cognitive engagement in the classroom.